From Palestine to Turtle Island - Sarah Rotz; Charles Levkoe; Martha Stiegman; Mustafa Koc; Indra Singh; Max Ajl; Yafa Al Masri; Justin Podur (Canadian Food Studies)
This paper examines the historical and ongoing role of food as both a tool of colonization and a means of liberation, focusing on Palestine and Turtle Island (Canada). In Gaza, the latest wave of Israeli military violence, described by the UN as genocidal, uses food militarization and weaponization as key tactics of settler colonial control. These strategies, rooted in colonial and capitalist systems, have long been employed by settler states like Canada to suppress Indigenous populations. The destruction of food systems in Palestine is part of a broader attack on land sovereignty, reflecting similar patterns of colonial land theft and environmental devastation in North America. Gaza now suffers from extreme food insecurity and famine, exacerbated by large-scale environmental destruction. Despite this, food sovereignty remains a crucial aspect of resistance for Palestinians and Indigenous peoples across the world. This paper draws on a panel discussion organized by the Canadian Association for Food Studies/L’Association canadienne des études sur l’alimentation (CAFS/ACÉA), featuring insights from three scholars who connect food systems to colonialism and struggles for self-determination. The discussion underscores the importance of Indigenous movements and mutual aid networks in the fight for land, food, and cultural sovereignty. These localized struggles are part of a larger global resistance against imperialism and colonialism, illustrating the power of food sovereignty as a means of survival and liberation.